Single locus genotyping to track Leishmania donovani in the Indian subcontinent: Application in Nepal - Rai, Keshav (PLoS Negl Trop Dis, 2017)
BACKGROUND: We designed a straightforward method for discriminating circulating Leishmania populations in the Indian subcontinent (ISC). Research on transmission dynamics of visceral leishmaniasis (VL, or Kala-azar) was recently identified as one of the key research priorities for elimination of the disease in the ISC. VL in Bangladesh, India, and Nepal is caused by genetically homogeneous populations of Leishmania donovani parasites, transmitted by female sandflies. Classical methods to study diversity of these protozoa in other regions of the world, such as microsatellite typing, have proven of little use in the area, as they are not able to discriminate most genotypes. Recently, whole genome sequencing (WGS) so far identified 10 different populations termed ISC001-ISC010. METHODOLOGY / PRINCIPLE FINDINGS: As an alternative to WGS for epidemiological or clinical studies, we designed assays based on PCR amplification followed by dideoxynucleotide sequencing for identification of the non-recombinant genotypes ISC001 up to ISC007. These assays were applied on 106 parasite isolates collected in Nepal between 2011 and 2014. Combined with data from WGS on strains collected in the period 2002–2011, we provide a proof-of-principle for the application of genotyping to study treatment outcome, and differential geographic distribution. CONCLUSIONS / SIGNIFICANCE: Our method can aid in epidemiological follow-up of visceral leishmaniasis in the Indian subcontinent, a necessity in the frame of the Kala-azar elimination initiative in the region.